PENGARUH JUMLAH TENAGA KERJA INDONESIA, INVESTASI DAN REMITANSI TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Fitri Indah Lestari, Ni Wayan; Budhi, Kembar Sri; Budhi, Kembar Sri (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
The Indonesian workforce placement program is one of the alternatives to reduce unemployment in the country. If the contribution of remittances from all TKIs is calculated, which is accompanied by improvements and improvements in the handling of TKI in the future, this sector should be the number one foreign exchange earner for the country capable of increasing economic growth. Economic growth also depends on the development of capital, the importance of investment is one of the main factors and determinants of economic growth. The purpose of this study was to determine the effect of the number of Indonesian workers, investment and remittances on Indonesia's economic growth. This research was conducted in the State of Indonesia. The type of data used is quantitative data with secondary data. Data collection was carried out through non-participant observation methods, which came from books, notes, and reports from related sources or agencies. The analysis technique used is multiple linear regression and moderated regression using time series data from 2006-2020. The results of this study indicate that all independent variables simultaneously and significantly influence Indonesia's economic growth. The results of the t-test study indicate that the variable number of formal TKI, informal TKI and investment has a positive and significant effect on Indonesia's economic growth, and remittances strengthen the effect of investment on Indonesia's economic growth.